(untitled) (Perner’s Contacts, 2014)
It is clear that the universal costs model of supplies, which could be used under any circumstances, does not exist. Like the businesses and the arrangement of their supply system differ, so it is necessary to adapt the individual components of the logistics costs model. The paper presents the draft basic - theoretical costs model containing all the main cost types that are relevant in the consideration of change in the supply system.